Perkembangan Teknologi dan Pengembangan Sumber Daya Manusia Lembaga Dakwah (Studi pada Lembaga Dakwah NU dan Muhammadiyah) - Nur Annisa Tri Handayani; Haki Algifari Jama (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2024)
It should be realized that the reality of the 21st century phenomenon in terms of the development of science and technology is absolutely necessary to be able to compete in the global world. In the development of technology and the development of human resources, Islamic propagation institutions are very important to be carried out in improving the abilities and skills of members of Islamic propagation institutions. In increasing the efficiency and productivity of Islamic propagation, the role of the government is very important in providing financial support and policies that facilitate the development of Islamic propagation technology. The method in this study uses a literature study with research results showing that the development of reliable and skilled human resources in technology is also very necessary to improve practical skills and overcome the challenge of the lack of skilled human resources in technology. Well-planned human resource development will produce quality output, so that it can increase work productivity and can prepare employees who are effective and efficient in carrying out their work.